Evaluation of the dosimetric and radiobiological parameters in four radiotherapy regimens for synchronous bilateral breast cancer. Issue 8 (21st June 2022) - Kang, Sang‐Won; Kang, Seonghee; Lee, Boram; Song, Changhoon; Eom, Keun‐Yong; Jang, Bum‐Sup; Kim, In Ah; Kim, Jae‐Sung; Cho, Woong; Shin, Dong‐Suk; Kim, Jin‐Young; Chung, Jin‐Beom
Abstract: This study is to investigate the optimal treatment option for synchronous bilateral breast cancer (SBBC) by comparing dosimetric and radiobiological parameters of intensity‐modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) plans using single and dual isocenters. Twenty patients with SBBC without lymph node involvement were selected retrospectively. Four treatment plans were generated for each patient using the Eclipse treatment planning system (Varian Medical System, Palo Alto, CA, USA) following two delivery techniques with two isocenter conditions—IMRT using a single isocenter (IMRT_Iso1), VMAT using a single isocenter (VMAT_Iso1), IMRT using dual isocenters (IMRT_Iso2), and VMAT using dual isocenters (VMAT_Iso2). A dose of 42.56 Gy in 16 fractions was prescribed for the planning target volume (PTV). All plans were calculated using the Acuros XB algorithm and a photon optimizer for a 6‐MV beam of a Vital Beam linear accelerator. PTV‐related dosimetric parameters were analyzed. Further, the homogeneity index, conformity index, and conformation number were computed to evaluate plan quality. Dosimetric parameters were also measured for the organs at risk (OARs). In addition, the equivalent uniform dose corresponding to an equivalent dose related to a reference of 2 Gy per fraction, the tumor control probability, and the normal tissue complication probability were calculated based on the dose–volume histogram to investigate the radiobiological impact on PTV and OARs. IMRT_Iso1 exhibited similar target coverage and a certain degree of dosimetric improvement in OAR sparing compared to the other techniques. It also exhibited some radiobiological improvement, albeit insignificant. Although IMRT_Iso1 significantly increased monitor unit compared to VMAT_Iso1, which is the best option in terms of delivery efficiency, there was only a 22% increase in delivery time. Therefore, in conclusion, IMRT_Iso1, the complete treatment of which can be completed using a single setup, is the most effective method for treating SBBC.